Phytochemical analysis of piper betle leaves extracts using fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS) using FTIR and GC-MS - Mohd Latiff, Nor Syahirah (2017)
Piper betle is known as a medicinal plant or herb serves as lead compounds for drug discovery and design. Piper betle may have various phytochemicals which lead to different biological activities used to treat various ailments. The choice of extraction solvents itself may affect the extractable components in the leaves of Piper betle. Therefore, the present study investigates the efficiency of various solvent extracts and the characterization of the bioactive constituents present in the leaf extracts of Piper betle using FTIR and GC-MS. The diluted crude extracts were scanned in the wavelength ranging from 4000-400 cm-1 by using Perkin Elmer Spectrophotometer and the characteristic peaks were detected. For GC-MS analysis, the diluted crude extracts filtered in ash less filter paper with 4 g sodium sulphate and the extract is concentrated to 1 ml by bubbling nitrogen into the solution. The compound detection employed the NIST Version 2.0 in Year 2005 library. The FTIR spectrum confirmed the presence of phenols, alcohols, alkanes, alkyl halides, carboxylic acids, aromatics, nitro compounds and amines in the three different extracts. The results of the GC-MS analysis provide different peaks determining the presence of phytochemical compounds with different therapeutic activities. There were 15 major compounds identified in the ethanolic leaves extract, followed by chloroform leaves extract (13 compounds) and the least phytochemicals found in the acetone leaves extract (10 compounds). In addition, the most compound found in ethanolic leaves extract was Caryophyllene (25.20%), acetone leaves extract was à-Phellandrene (7.20%) while in chloroform leaves extract was Humulane-1,6- dien-3-ol (6.63%). Thus, the result of this study will make a way for the production of herbal medicines for various ailments by using Piper betle leaves and lead to further discovery of new drugs for modern treatment